The Slotted Tube Overlay Geotextile in Tailing Pond Radial Seepage Test Model and Analysis of the Permeation Characteristics. (21st October 2021) - Yang, Chun-bo; Wang, Yuan; Wang, Lin-bing; Huang, Jing-qi; Li, Qing-wen; Wu, Long
Abstract : Slotted tube drainage system plays an important role in reducing the wetting line of tailing dam. In the past studies, the permeability coefficient of geotextile was measured separately based on one-dimensional test, and the permeability characteristics of the whole system of the slotted tube overlay geotextile were rarely studied. Firstly, a set of radial flow test equipment for infiltration system of the slotted tube overlay geotextile is developed in this study. Then, with the aid of the test device, a two-dimensional radial flow test is conducted to investigate the drainage system of the slotted tube overlay geotextile before and after blocking by tailing sands, with considering different water head difference and the number of geotextile layers. By the two-dimensional radial flow test, it can be concluded that (1) the permeability coefficients of the slotted tube overlay geotextile before and after blocking all have a slight upward trend with the increase of water head difference; (2) with increasing the number of geotextile layers, the permeability coefficients before and after blocking increase first and then decrease, which approaching its minimum value at about two layers; (3) under the seepage pressure, some particles might attach to or stay in geotextile. Therefore, the permeability coefficient of the slotted tube overlay geotextile after blocking is significantly smaller than that before blocking. This study offers the insight to the further research on the permeation characteristics of the slotted tube overlay geotextile system.